Pengaruh Pendidikan Kesehatan Media Booklet terhadap Tingkat Kecemasan Premenopause di Kelurahan Karangayu Semarang - Rema Putri Anganthi; Rinda Intan Sari; Vivi Sovianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Premenopause is a transitional phase that women experience towards menopause. This phase is a physiological condition in women who have entered the aging process, characterized by a decrease in hormonal levels of estrogen in the ovaries. Premenopause occurs when women are aged between 39–51. Anxiety is the most common psychological problem faced by women in premenopause. This pre-experimental research determined the influence of the impact of health education media booklets on premenopausal anxiety rates among a sample of 46 respondents with a one-group pretest-posttest design. The researcher conducted a design evaluation to assess anxiety levels before and after receiving health education through a media booklet on physical and psychological changes during premenopause. The results showed that the minimum age of respondents was 40 and the maximum was 48. Most respondents were high school learners, 31 respondents. The Wilcoxon test yielded a value of 0.000, indicating a significant influence of the health education media booklet on the premenopausal anxiety rate in Karangayu village, Semarang. The researcher expects mothers nearly to the premenopause period to comprehend the signs and symptoms of premenopause, relying on verifiable information, to effectively manage this period.